PERAN CUSTOMER SERVICE DALAM MENINGKATKAN KEPUASAN PELANGGAN MELALUI PENDEKATAN KOMUNIKASI ANTAR PRIBADI (Studi Kasus pada Customer Service GraPARI Telkomsel Gandaria) - Tarsani Tarsani (Universitas Bunda Mulia, 2016)
Communication is a statement and a technique of how a communicator deliver a message tocommunicant. At this point, communication process in delivering message or information itselfoccures when a customer service officer serves a customer or in other words, the process takes placein direct communiation activity with the customers. Customer service has role as the the front line ofthe company and the connector between company and its customers. It has become the duty andresponsibility for a company to provide service in the terms of product information,consultation,handling complaints, after sales service, and so on. In delivering message and informaionto customers, a customer service officer must have competency in communicating the information andsolution related to customer needs and complaints, so that the customer satisfaction can be attained.This matter has attracted the writer to do a reasearch entitled “The Role of Customer Service inIncreasing Customer Satisfaction by means of interpersonal Approach”. This research applies casestudy method and qualitative research approach. Regarding to the character of this research, thewriter gives description about research topic which is derived from data source; in forms of interviewsand observations. On the other hand, this research also applies interpretive paradigm andinterpersonal communication theory by Deddy Mulyana, Theory of coordinated meaning managementby West & Turner.Keywords: Customer Service, Cutomer Satisfaction, Interpersonal Communication